Wytyczne KW PZPR w Zielonej Górze w sprawie przeprowadzenia kampanii wyjaśniającej w związku z wynikami radziecko-niemieckich rokowań w 1953 roku = The guidelines by KW PZPR in Zielona Góra on the information campaign in connection with the Soviet-German talks in 1953 - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On 20-22 August, 1953, in Moscow, negotiations were held between the Soviet governmentand the GDR government delegation. The Polish society suspected that behind the scenes there were talks about the revision of Poland's western border, running along the Nysa and theOdra rivers. The party and state authorities feared the inhabitants of the Recovered Territories might be thrown into a panic. Measures bad to be taken to reassure the Polish society.
Keywords: Zielona Góra (okręg); PZPR (Polska Zjednoczona Partia Robotnicza); stosunki polsko-niemieckie; stosunki niemiecko-rosyjskie; Ziemie Zachodnie i Północne